Diagnostic and prognostic value of angiography-derived index of microvascular resistance: a systematic review and meta-analysis - Wang, Dayang; Li, Xiaoming; Feng, Wei; Zhou, Hufang; Peng, Wenhua; Wang, Xian (Frontiers in Cardiovascular Medicine, 2024)
Background The angiography-derived index of microvascular resistance (A-IMR) is a novel tool for diagnosing coronary microvascular dysfunction (CMD) addressing limitation of unavailability. However, the clinical value of A-IMR remains controversial. Methods A systematic review and meta-analysis was conducted. PubMed, EMBASE, Cochrane Library and Web of Science were searched for relevant studies. Studies that reported estimates of A-IMR's diagnostic accuracy (with thermodilution-based IMR as the reference test) and/or predictions of adverse cardiovascular events were selected. Pooled sensitivity, specificity, area under the summary receiver operating characteristic curve (sROC) were calculated to measure diagnostic performance; pooled hazard/risk ratio (HR/RR) and 95% confidence interval (95% CI) of major adverse cardiovascular events (MACE) or other independent adverse events were calculated to measure prognostic effect. This study was registered with PROSPERO (CRD42023451884). Results A total of 12 diagnostic studies pooling 1,642 vessels and 12 prognostic studies pooling 2,790 individuals were included. A-IMR yielded an area under sROC of 0.93 (95% CI: 0.91, 0.95), a pooled sensitivity of 0.85 (95% CI: 0.79, 0.89) and a pooled specificity of 0.89 (95% CI: 0.83, 0.93) for the diagnosis of CMD. CMD diagnosed using A-IMR was associated with higher risks of MACE (HR, 2.73, 95% CI: 2.16, 3.45), CV death (RR, 2.39, 95% CI: 1.49, 3.82) and heart failure hospitalization (HR, 2.30, 95% CI: 1.53, 3.45). Conclusion A-IMR demonstrated high diagnostic accuracy for CMD and showed a strong prognostic capability in predicting the risk of adverse CV outcomes. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023451884, PROSPERO (CRD42023451884).